The effect of using a cognitive reinforcement strategy on improving performance in running (Secondary school students) - LARACHI, Mohamed; ZERAOULA, Ali; GOUMIDI, Mohamed Amine (The International tax journal, 2026)
The study aimed to identify the role of cognitive motivation in improving running performance among students of the second educational stage. The experimental method was employed, involving two independent groups (experimental and control), with a total sample of 44 students. A comprehensive training program was implemented, combining physical preparation and cognitive development. This program focused on learning to retain execution plans, maintaining concentration, providing feedback, and correcting errors in each instructional situation. The results revealed statistically significant differences in favor of the experimental group between the pre-test and post-test measurements. The study recommended the adoption of cognitive motivation during training to improve performance outcomes, and emphasized the importance of using scientific principles in training and performance in order to properly identify and correct errors.